Torture Is the Ticking Time-Bomb: Why the Necessity Defense Fails - Hunsinger, George (Dialog, 2008)
The essay asks whether the ‘necessity defense’ can be used to legitimate torture. By modifying the criteria so as to fit the case, it is argued that torture fails to meet the established norms of the historic just-war tradition, which also underlie international law. ‘Interrogational,’‘terroristic,’ and ‘demonic’ aspects of torture are distinguished along the way. It is concluded that torture admits no necessity by which it can be justified.